Concept Maps for Teaching-Learning : An Analysis of Teachers’ Classroom Practices and Perspectives - Suhane, Anjuli; Joshi, Vibha (INDIAN EDUCATIONAL REVIEW, 2021)
The present research attempts to examine teachers’ perspective and classroom practices in the use of concept maps in teaching-learning, assessment and the scores of assessment of the use of concept maps. Main objectives were to analyse teachers’ classroom practices regarding the use of concept maps, their views about the use of concept maps in planning, teaching-learning and assessment tools and to find out a scoring system adopted by teachers to assess learner’s learning through concept maps. A questionnaire was administered to 205 purposefully selected secondary school teachers from Bhopal district of Madhya Pradesh, India. The study revealed that about one third of teachers had used concept mapping as an approach for transaction purposes but a negligible or a few of them had used it as a tool for assessment. According to teachers concept map is a useful, effective and practical tool for transacting or teaching concepts; helps in retention and recall of concepts by learners and provides detailed feedback on the understanding of the concepts learnt. It was also found that the concept map was more valuable for formative assessment rather than summative assessment. Majority of the teachers reported that assessment through concept maps is a rigorous and time consuming process.